High-temperature terahertz quantum cascade lasers. (November 2021) - Wen, Boyu; Ban, Dayan
Abstract: The terahertz (THz) quantum cascade laser (QCL), first demonstrated in 2002, is among the most promising radiation sources in the THz region owing to its high output power and broad frequency coverage from ∼1.3 to ∼5.4 ​THz and sub-terahertz, without and with assistance of external strong magnetic field. The operation of THz QCLs, however, has thus far been limited to applications below room temperature. Recent advances in THz QCL research have principally focused on optimization of quantum design, fabrication, and growth techniques to improve the maximum operating temperature of THz QCLs; these efforts culminated in a recent demonstration of pulse-mode lasing at temperature up to 250 ​K. Research interests continue to be propelled as new maximum lasing temperature record are set, heating up the race to realize room-temperature operation of THz QCLs. This paper critically reviews key achievements and milestones of quantum designs, fabrication techniques, and simulation methods applicable to the high temperature operation of THz QCLs. In addition, this paper provides a succinct summary of efforts in this field to pinpoint the remaining challenges and provide a comprehensive picture for future trends in THz QCL research.